Effects of Quantity and Size of Buttons of In-Vehicle Touch Screen on Drivers' Eye Glance Behavior. Issue 12 (2nd December 2018) - Feng, Fred; Liu, Yili; Chen, Yifan
ABSTRACT: This article investigates the effects of the quantity and size of touch screen buttons and the task-interleaving strategies on drives' eye glance behavior. An experiment was conducted on a fixed-base driving simulator with 20 participants. The participants were asked to perform a button search-and-press task on an in-vehicle touch screen while driving. A full-factorial within-subject design was used with three button quantities (4, 8, and 15) and three button sizes (14 mm, 24 mm, and 33 mm). Although a normal distribution was often assumed for the eye glance data in previous studies, our results show that the total eyes-off-road time (TEORT) and glance durations are generally not normally distributed (positively skewed) even after a log transformation. The results show that the number of buttons has an increasing effect on task completion time, TEORT, and long (2+ s) glances. However, in general, no such differences were found for button sizes. Further analysis shows that long glances were strongly associated with drivers completing the task with a single glance. It seems to suggest that a major cause of long glances is that drivers are reluctant to switch the task back to driving at subtask boundaries that are probably associated with the high cost of interruption. These findings confirm the importance of task resumability for in-vehicle user interfaces and have implications that careful task analysis needs to be conducted in the context of multitasking. Certain subtask combinations, such as a visual search followed by pressing the search target, may discourage task interleaving and ultimately compromise driving safety.